A look at the hidden curriculum of a psychology career - de la Paz Grebe, María (2020)
This research explores the hidden curriculum of a psychology career at an Argentine private university. It explores the learnings neither specifics nor anticipated that happened during the study of the career. The qualitative methodology is used, based on interviews in fifteen students, as information source. Five dimensions are identified in the hidden curriculum: hospital, humanity formation, centrality of the person, institutional logic and psychologist of this university. These are related to the context (physical and emotional) of the school, except for what is called a university´s psychologist that encompasses the professional identity. The findings confirm the existence of a hidden curriculum of this psychology career; however, it is necessary to broaden the exploration in the perspective including new actors and other methodological strategies.